Current Trends of Surface Science and Catalysis - Park, Jeong Young.; Park, Jeong Young. (Springer New York : Imprint: Springer, 2014)
This unique book covers the latest surface science studies on model catalysts, including single crystals, non-colloidal nanocatalysts, and nanoparticles in various forms with the control of size, shape and composition. This book addresses the issue of bridging “materials and pressure gaps” and also discusses the important issue of metal-oxide interface and hot electron flows in heterogeneous catalysis. The current development of in-situ surface techniques that is relevant to bridging “pressure gaps” is also highlighted. This book also: Provides a comprehensive view on materials (covering single crystal, nanoparticles, and nanostructures) and techniques (both ex-situ and in-situ surface apparatus) of surface science Discusses the role of metal-oxide interface, surface oxides and hot electron flows in heterogeneous catalysis and surface chemistry Covers the application of surface science in the renewable energy conversion Current Trends of Surface Science and Catalysis is an ideal book for graduate students and researchers in the field of surface science and catalysis.